Clinical characteristics of acalypha indica poisoning - Aimon Pradoo (2020)
© 2020 Pradoo et al. Background: Acalypha indica is a tropical plant used as a herbal medicine in various parts of the world, including Thailand. In glucose-6-phosphate dehydrogenase (G6PD)-deficient patients, acute hemolysis has been reported following the ingestion of this plant. Methemoglobinemia was reported in the present study. Patients and Methods: Descriptive data of patients who suffered from Acalypha indica toxicity reported from different hospitals to the Ramathibodi Poison Center were retrieved from 2011 to 2019. Results: Eight patients were included, mostly male with a median age of 61.5 years. The plant was ground for fresh juice or boiled before consuming as herbal medicine. All patients presented with dark urine. Most had jaundice and fever, and all reported hemolysis. Seven out of eight patients were diagnosed as methemoglobinemia. Methemoglobin level was confirmed in five patients with the highest level of 23.9%. Early symptoms occurred within 24 hours of the last ingested dose. Discussion: In previous case reports of Acalypha indica ingestion, acute hemolysis was mostly observed in G6PD-deficient patients, consistent with the current findings. However, our patients also demonstrated methemoglobinemia, with some constituents in this plant (quinine, 2-methyl anthraquinone and tectoquinone) implicated as the cause in previous studies. Further studies are crucial to validate these findings. Conclusion: We report a case series in which acute hemolysis and methemoglobinemia after Acalypha indica ingestion were observed. This study presents methemoglobinemia as the other toxicity caused by this plant.